2009
DOI: 10.1007/s12010-009-8558-3
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Osteoblast Differentiation is Negatively Regulated by Hoxc8

Abstract: Hoxc8 has multiple roles in normal skeletal development. In this paper, a MC3T3-E1 subclone 4 osteogenic cell differentiation model was used to examine expression of Hoxc8 at multiple stages of osteogenesis. We found that Hoxc8 expression levels do not change in the early stage but increase in the middle stage and decrease in the late stage of osteogenesis. A knockdown of Hoxc8 by small-interfering RNA transfection in C2C12 cells indicated that Hoxc8 is a negative regulator of osteogenesis. Similarly, expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…miR‐196 family members play important roles in the proliferation and osteogenic differentiation of cells (Kim et al., ). Previous studies have shown that overexpression of miR‐196a could enhance osteogenic differentiation, and promote the commitment of mesenchymal stem cells to the osteoblast lineage through targeting HOXC8 (MIM# 142970) gene, which is essential for osteoblast differentiation (Kim et al., ; Zheng et al., ). In this study, FGF2 was experimentally validated as an in vitro target, which suggests a potential regulation mechanism by which hsa‐miR­196a‐3p was involved in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐196 family members play important roles in the proliferation and osteogenic differentiation of cells (Kim et al., ). Previous studies have shown that overexpression of miR‐196a could enhance osteogenic differentiation, and promote the commitment of mesenchymal stem cells to the osteoblast lineage through targeting HOXC8 (MIM# 142970) gene, which is essential for osteoblast differentiation (Kim et al., ; Zheng et al., ). In this study, FGF2 was experimentally validated as an in vitro target, which suggests a potential regulation mechanism by which hsa‐miR­196a‐3p was involved in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the Hox genes (Hoxb8, Hoxc8, Hoxd8, Hoxa7), miR-196 family members play a crucial role in development of the axial skeleton, fine-tuning levels of HOX proteins in a temporal and spacial manner [70-76]. miR-196a promotes commitment of mesenchymal stem cells (MSCs) towards the osteoblast lineage by targeting Hoxc8 [77, 78].…”
Section: Mir-snps: Snps In Mirna Genes Altering Their Biogenesis Amentioning
confidence: 99%
“…miR-196a promotes commitment of mesenchymal stem cells (MSCs) towards the osteoblast lineage by targeting Hoxc8 [77, 78]. In osteoblasts, Hoxc8 acts as a negative regulator of differentiation and transcriptionally suppresses osteopontin [72, 73, 76]. In turn, BMP signaling represses Hoxc8 activity through SMAD1 interaction with Hoxc8, relieving repression of osteopontin transcription.…”
Section: Mir-snps: Snps In Mirna Genes Altering Their Biogenesis Amentioning
confidence: 99%
“…In many studies, enamel matrix derivative enhanced the proliferation of osteoprogenitors , whilst numerous studies found that their differentiation (estimated by measuring alkaline phosphatase activity, expression of alkaline phosphatase, osteocalcin or core‐binding factor alpha‐1 or biomineralization) was invariably stimulated by enamel matrix derivative . Obviously, these cells were used to test the possible stimulatory effects of other biomolecules, such as bone morphogenetic protein‐2 and bone morphogenetic protein‐7 .…”
Section: In Vitro Models Of Periodontal Regenerationmentioning
confidence: 99%